CFD calculations of flow, dispersion and chemical reactions in fixed bed tubular reactors using the lattice Boltzmann method - Freund, Hannsjörg; Zeiser, Thomas; et al. (High Performance Scientific and Engineering Computing, Lecture Notes in Computational Science and Engineering, 2002)
Detailed 3-D simulations are required to correctly predict the coupled behaviour of flow and mass transport in chemical reactors with e-asymmetry. These simulations can be of great technical and economical interest as the reactor performance and safety during operation are significantly influenced by the local flow behaviour. One particular interesting example are randomly filled tubular fixed bed reactors with small tube-to-particle diameter ratios. New numerical methods such as the lattice Boltzmann approach together with the increasing computational power can provide detailed insight into the flow and transport processes in complex geometries. The present paper demonstrates the applicability of this approach by investigating complex flows and showing first results of the inhomogeneities in the 3-D flow of reacting species in a tubular fixed bed reactor.